2021
DOI: 10.3390/clinpract11030083
|View full text |Cite
|
Sign up to set email alerts
|

Dilated Cardiomyopathy Associated with Paraquat Herbicide Poisoning

Abstract: Dilated cardiomyopathy is a subset of cardiomyopathies defined by reduced ejection fraction of less than 45% and a dilated left ventricle. While dilated cardiomyopathy is common, its etiology is not always readily evident. Paraquat is used as an herbicide worldwide and is one of the main causes of fatal poisoning in underdeveloped countries in Asia, Central America, and the Pacific Islands. The most commonly affected organs are the lungs and kidneys. However, experimental research has shown that Paraquat can a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Studies have revealed a close association between paraquat poisoning and alterations in in ammatory cytokines. The elevation in toxin concentration is correlated with an increase in in ammatory cytokines, and as time progresses, the levels of in ammatory cells consistently rise, demonstrating dynamic changes throughout the entire experiment [34]. The primary molecular mechanism underlying paraquat toxicity involves disruption of the body's REDOX system and induction of intracellular oxidative stress.…”
Section: Visualization System Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have revealed a close association between paraquat poisoning and alterations in in ammatory cytokines. The elevation in toxin concentration is correlated with an increase in in ammatory cytokines, and as time progresses, the levels of in ammatory cells consistently rise, demonstrating dynamic changes throughout the entire experiment [34]. The primary molecular mechanism underlying paraquat toxicity involves disruption of the body's REDOX system and induction of intracellular oxidative stress.…”
Section: Visualization System Constructionmentioning
confidence: 99%
“…Consequently, serum creatinine serves as a reliable indicator of renal function and exhibits a close association with prognosis among patients suffering from acute paraquat poisoning [33]. The administration of Paraquat may induce activation of the sympathetic-adrenal medulla axis, leading to a redistribution of renal blood ow from the cortex to predominantly supply the medulla, thereby resulting in an elevation in serum creatinine levels [34]. By inducing proximal renal tubule destruction, paraquat disrupts the mitochondrial transmission chain and instigates the generation of reactive oxygen species.…”
Section: Visualization System Constructionmentioning
confidence: 99%
“…Dear Editor, Poisoning with paraquat, a highly lethal herbicide, is often encountered in developing countries [1]. Human intoxication by paraquat typically occurs due to ingestion either accidentally or with suicidal intent and rarely following dermal exposure [2]. The high case fatality rate is due to lack of an effective antidote and the inherent cellular toxicity of paraquat, which is secondary to oxidative stress [3,4].…”
mentioning
confidence: 99%